Long-term consequences of atrial fibrillation after aortic valve replacement. (March 2017) - Kohno, Hiroki; Ueda, Hideki; Matsuura, Kaoru; Tamura, Yusaku; Watanabe, Michiko; Matsumiya, Goro
Background: Atrial fibrillation is a common complication after cardiac surgery, but the risk factors and long-term outcome after primary isolated aortic valve replacement remains to be clarified. Methods: A single-center retrospective study was conducted on 157 patients who underwent first-time isolated aortic valve replacement between April 1999 and February 2015. Fifty-eight patients developed new-onset atrial fibrillation within 6 months postoperatively, and they were compared with patients who remained in sinus rhythm. Multivariate analyses, which incorporated the propensity score patient matching technique, were conducted to evaluate the long-term outcome of new-onset postoperative atrial fibrillation and identify patients at risk of developing this arrhythmia. Results: At a mean follow-up of 52.4 months (range 8.4–200.7 months), mortality was significantly higher in patients who developed atrial fibrillation compared to those who remained in sinus rhythm (2.8%/patient-year vs. 0.2%/patient-year, respectively; p < 0.05). Patients developing atrial fibrillation were also at an independently increased risk of stroke and readmission during follow-up. Risk analysis revealed that advanced age (>70 years) and absence of a postoperative β-blocker were predictors of atrial fibrillation. Conclusions: New-onset atrial fibrillation after first-time isolated aortic valve replacement correlated significantly with late morbidity and mortality. Advanced age and absence of a postoperative β-blocker may increase the incidence of atrial fibrillation.